1998
DOI: 10.1063/1.368146
|View full text |Cite
|
Sign up to set email alerts
|

Charge injection into light-emitting diodes: Theory and experiment

Abstract: An analytic theory is presented for dark injection from a metallic electrode into a random hopping system, e.g., a conjugated polymer or a molecularly doped polymer. It encompasses injection of a charge carrier from the Fermi level of the electrode into tail states of the distribution of hopping states of the dielectric followed by either return of the charge carrier to the electrode or diffusive escape from the attractive image potential. The latter process resembles Onsager-type geminate pair dissociation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
238
0
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(253 citation statements)
references
References 24 publications
8
238
0
7
Order By: Relevance
“…The effect of these image dipoles is to reduce the disorder close to the electrodes. 34 This leads to a reduced current, because the effect of enhanced injection into energetically low-lying states in the organic material 35 is less. This reduction only occurs for high injection barriers.…”
Section: Results For Current-voltage Characteristicsmentioning
confidence: 99%
“…The effect of these image dipoles is to reduce the disorder close to the electrodes. 34 This leads to a reduced current, because the effect of enhanced injection into energetically low-lying states in the organic material 35 is less. This reduction only occurs for high injection barriers.…”
Section: Results For Current-voltage Characteristicsmentioning
confidence: 99%
“…A Monte Carlo simulation shows that the initial jump is essential and determines the temperature and field dependence of the injection process. [9][10][11] The injection-limited current density J ͑ILC͒ can then be analytically approximated by averaging the product of the frequency of the initial jumps of the charge carrier across the metal-polymer interface and the probability to escape recombination, over all site energies E and the initial jump distances x. Arkhipov et al have shown that the ILC can be described by [9][10][11] …”
Section: Resultsmentioning
confidence: 99%
“…It has been recently demonstrated 8 that the hole injection into OC 1 C 10 ϪPPV is consistently described by a hopping based model, which takes full account of both positional and energetic disorder of the system and image force effect. [9][10][11] According to this model a charge carrier will make an initial jump from the Fermi level of the metal into localized states close to the metal-semiconductor interface, followed by either a diffusive escape from the interface or a backflow to the metal. A Monte Carlo simulation shows that the initial jump is essential and determines the temperature and field dependence of the injection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The field and temperature dependence of the injection-limited ͑IL͒ current is consistently explained by an injection model based on injection into tail states of the energetic distribution of hopping sites. 8 In this letter, the role of an injection barrier on the performance of a PLED is investigated by incorporating the hopping-based injection mechanism in the device model. The current and light output of an IL PLED have experimentally been investigated for a PPV-based PLED with limited hole injection from a Ag anode.…”
Section: Electro-optical Properties Of a Polymer Light-emitting Diodementioning
confidence: 99%